2016
DOI: 10.3406/ecmed.2016.1229
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sowing methods on growth and root deformations of containerized cork oak (Quercus suber L.) seedlings in nursery

Abstract: This work consists on the study of the effects of some sowing methods of cork oak acorns on seedling performances. We studied the effects of acorns which germinated during storage, acorns which did not germinate during storage, acorns which germinated after moist stratification, arrangement of acorns in container and orientation of the radicle on seedling survival, growth and types of root deformations. To do so, a completely three-block randomized design was installed in nursery. After eight months of growth,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Although, both treatment combinations cause root deformation, the germination status of acorns at the time of sowing was shown to exert the most significant effect. In accordance with a previous research (Chouial and Benamirouche, 2016), the greatest number of deformed roots was observed on seedlings grown from sowing of germinated acorns than on seedlings grown from direct sowing of intact acorns with respective percentages of 91% and 9% of the inspected seedlings. Thus, direct sowing of intact acorns could significantly reduce the occurrence of root deformations.…”
Section: Discussionsupporting
confidence: 92%
“…Although, both treatment combinations cause root deformation, the germination status of acorns at the time of sowing was shown to exert the most significant effect. In accordance with a previous research (Chouial and Benamirouche, 2016), the greatest number of deformed roots was observed on seedlings grown from sowing of germinated acorns than on seedlings grown from direct sowing of intact acorns with respective percentages of 91% and 9% of the inspected seedlings. Thus, direct sowing of intact acorns could significantly reduce the occurrence of root deformations.…”
Section: Discussionsupporting
confidence: 92%